INDICATORS FOR DETERMINING THE HYGIENIC CONDITION OF DENTAL PROSTHESES - Qobilov R. I.; Saidov A. A. (Central Asian Journal of Medical and Natural Science, 2024)
Relevance. Removable plate and clasp prostheses help to restore chewing, speech functions and normalize aesthetics, provide good hygienic care. However, through the base of the prosthesis, they negatively affect the tissues of the prosthetic limb and preserved teeth. When using thermoplastic prostheses, a significant part of the chewing pressure is redistributed to the base teeth. Removable lamellar prostheses minimally transfer chewing pressure to the preserved teeth, since the main part of the pressure falls on the mucous membrane of the alveolar process or alveolar part and bone tissue. With high chewing pressure under the base of the prosthesis, metabolic processes in the tissues of the alveolar tumor or the alveolar part change, which manifest themselves in the form of tissue atrophy. When using removable dentures, atrophic processes of the alveolar tumor and the alveolar part are observed.